Performance evaluation of software‐defined wide area network based on queueing theory. Issue 3 (5th July 2022) - Ibrahim Hussein, Samaa Adel; Zaki, Fayez Wanis; Ashour, Mohammed M.
Abstract: Software‐defined wide area network (SD‐WAN) is part of wider technologies of software‐defined networking (SDN). SDN is one of the pivotal network management approaches that abstracts the underlying network infrastructure away from its applications. SDN allows for the centralisation of network intelligence. That allows higher network automation, the simplification of operations, the provisioning, the monitoring, and the troubleshooting. These days, data volume that enterprises and users make is growing rapidly and continuously. As a result, wide area networks are growing increasingly and they are becoming very complicated to manage and monitor using traditional tools. So, many enterprises are interested in developing SD‐WAN and benefiting from its advantages. To achieve this goal, a proposed model for the SD‐WAN network will be presented based on the queueing theory; then, the proposed model will be analysed using the Quasi‐birth–death approach to evaluate traffic behaviour of a proposed queueing model for Poisson distribution in the SD‐WAN. Moreover, it compares Poisson to phase type distribution via calculating some parameters that influence traffic behaviour of those distributions in the SD‐WAN. The analysis results indicate that the proposed queueing model displays a more accurate SD‐WAN controller performance than the existing ones.